2005
DOI: 10.1029/2004wr003412
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic analysis of steady state two‐phase flow in heterogeneous media

Abstract: [1] We present a novel approach to modeling stochastic multiphase flow problems, for example, nonaqueous phase liquid flow, in a heterogeneous subsurface medium with random soil properties, in particular, with randomly heterogeneous intrinsic permeability and soil pore size distribution. A stochastic numerical model for steady state water-oil flow in a random soil property field is developed using the Karhunen-Loeve moment equation (KLME) approach and is numerically implemented. An exponential model is adopted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…Log intrinsic permeability, log pore size distributions, and log van Genuchten fitting parameter are treated as input stochastic properties, distributed normally with a separable exponential covariance function. The Karhunen-Loeve expansions of these stochastic input variables was presented in Chen et al (2005Chen et al ( , 2006 for two-phase flow, and the application to three-phase flow follows that expansion. Monte Carlo (MC) simulations are conducted to confirm the validity of the KLME analysis and its numerical implementation.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Log intrinsic permeability, log pore size distributions, and log van Genuchten fitting parameter are treated as input stochastic properties, distributed normally with a separable exponential covariance function. The Karhunen-Loeve expansions of these stochastic input variables was presented in Chen et al (2005Chen et al ( , 2006 for two-phase flow, and the application to three-phase flow follows that expansion. Monte Carlo (MC) simulations are conducted to confirm the validity of the KLME analysis and its numerical implementation.…”
Section: Introductionmentioning
confidence: 95%
“…A novel stochastic approach based on the Karhunen-Loeve expansion and perturbation method (KLME) has been implemented in saturated flow and unsaturated one-phase flow by Zhang and Lu (2004) and Yang et al(2004). Chen et al (2005Chen et al ( , 2006 introduced KLME method to complex multiphase flow systems, and predicted mean and variance of fluid pressures, capillary pressure and saturations for the water-oil flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C a (x,y) is symmetrical and positive definite, whose eigenfunctions are mutually orthogonal and form a complete set spanning the function space to which a(x,h) belongs (Ghanem and Dham 1998). The mean-removed stochastic process a 0 (x,h) can be expanded as follows (Karhunen 1947;Loève 1948;Zhang and Lu 2004;Chen et al 2005):…”
Section: Kl Decomposition Of Conditional Random Fieldmentioning
confidence: 99%
“…Yang et al (2004) extended KLME to analysis of saturated-unsaturated flow described by Richard's equation. Chen et al (2005Chen et al ( , 2006 developed a stochastic multiphase flow model following the same approach. These studies demonstrated the accuracy and efficiency of KLME over traditional Monte Carlo simulation or other stochastic moment approaches.…”
Section: Introductionmentioning
confidence: 99%